UNSUR INTRINSIK DALAM NASKAH DRAMA SANG MANDOR KARYA RAHMAN ARGE (Intrinsic Component in Sang Mandor By Rahman Arge) - Nasruddin Rauf (Balai Bahasa Sulawesi Selatan, 2009)
“Sang Mandor” by Rahman Arge is a text written the based on reality in sociallife, although imagination aspect is more conspicuous. The Aim of this writing isto describe instrinsic aspect in text of drama Sang Mandor. The plot described inthe story shows chronological life or logicet plot. Character in the drama isinteraction among human; setting consists of nature setting happen in Macassar,time setting, social setting which, Sang Mandor Theme is egoist way of life.Instrinsic aspect found in text of drama Sang Mandor by Rahman Arge is aspectthat interrelates and forms a whole structural aspect which can not be separatedwith the other.